(untitled) (Comparative & International Education Series, 2023)
Breaking Barriers: The Inspiring Stories of African American Women is a collection of inspiring and uplifting stories that celebrate the achievements of 19 remarkable women at Morgan State University who broke down barriers and shattered stereotypes. From scientists and educators to artists and activists, these women have made a significant impact in their fields and the world around them. Through their perseverance, resilience, and determination, they have changed the course of history and paved the way for generations to come. This book is a testament to the power of perseverance and a celebration of the incredible accomplishments of African American women at Morgan State University.